The Effectiveness Of The Rural Empowerment and Agricultural Development Scaling-Up Initiative (READSI) in Bone Bolango Regency - Mohammad Ridwan Matoka; Mahludin Baruwadi; Supriyo Imran; Abdul Fajar Haras (Citakonsultindo, 2026)
The agricultural sector plays a strategic role in developing countries, including Indonesia. This sector employs a large workforce in both the formal and informal sectors. Its contribution to both the national and regional economies cannot be underestimated. As one of the flagship programs of READSI (Rural Empowerment and Agricultural Development Scaling-Up Initiative), it aims to improve the welfare of farmers through their economic empowerment. Bone Bolango Regency is one of the regions participating in this program and has implemented the following components: Rural Agriculture and Livelihood Development, Improved Extension Services, Provision of Agricultural Inputs and Marketing Support, Availability of Policy and Development Strategy Support, and Program Management Support. Therefore, a study is needed to assess the effectiveness of the READSI program and identify its constraints. This study was conducted in Bone Bolango Regency using qualitative descriptive analysis in accordance with the Miles and Huberman model, which involves data collection, data reduction, data presentation, and drawing conclusions. There were 22 informants consisting of stakeholders (the Head of the Agency and extension workers), actors (READSI program facilitators), and program beneficiaries (farmers’ group leaders and farmers). The results of this study indicate that: 1). The evaluation of the READSI program’s effectiveness, as assessed from the input aspect (budgetary support, extension workers, and production facilities), the process aspect (implemented using a participatory approach and group-based learning), and the output aspect (farmers experienced increased income). 2). The factors hindering the implementation of the READSI Program include: low technology adoption rates among farmers, limited production facilities and supporting infrastructure, delays in aid distribution, lack of support from the village government, and limited market access.